FAKTOR-FAKTOR YANG MEMENGARUHI CONSUMER'S PURCHASE BEHAVIOUR TERHADAP PRODUK CLOTHING ERIGO DI INDONESIA - Andrew Christopher Limantara; Andhy Setyawan; Hayuning Purnama Dewi (CALYPTRA, 2025)
Abstract—This study aims to understand several factors that influence the purchasing behavior of Erigo consumers in Indonesia. The object used in this study is the level of purchase of Erigo clothing products in Indonesia. The data contained in the study were processed using the Structural Equation Modeling (SEM) research model through AMOS version 24.0 software. The results showed that the factors of brand consciousness, brand awareness, and brand nationality have a positive and significant effect on consumer's purchase behavior. The factors of brand consciousness and brand nationality have no effect on brand awareness in this study. The brand schematicity factor also has no effect on consumer's purchase behavior. Keywords: consumer’s purchase behaviour, brand awareness, brand schematicity, fashion clothing brands, clothing product Abstrak—Penelitian ini bertujuan untuk memahami beberapa faktor yang berpengaruh terhadap perilaku pembelian konsumen Erigo di Indonesia. Objek yang digunakan dalam penelitian ini yaitu tingkat pembelian produk clothing Erigo di Indonesia. Data yang terdapat dalam penelitian diolah dengan menggunakan model penelitian Structural Equation Modeling (SEM) melalui software AMOS versi 24.0. Penelitian ini mencakup 150 responden dengan karakteristik konsumen produk clothing Erigo sebagai data primer. Hasil penelitian menunjukkan bahwa faktor brand consciousness, brand awareness, dan brand nationality berpengaruh positif dan signifikan terhadap consumer’s purchase behaviour. Faktor brand consciousness dan brand nationality tidak berpengaruh terhadap brand awareness dalam penelitian ini. Faktor brand schematicity juga tidak berpengaruh terhadap consumer’s purchase behaviour. Kata kunci: consumer’s purchase behaviour, brand awareness, brand schematicity, fashion clothing brands, clothing product